Reproductive characteristics, population genetics, and pairwise kinship inform strategic recovery of a plant species in a fragmented landscape. Issue 4 (22nd February 2023) - Doyle, Chantelle A. T.; Yap, Jia‐Yee Samantha; Bragg, Jason; Rossetto, Maurizio; Orme, Andrew; Ooi, Mark J. K.
Abstract: Population genetics and understanding of mating systems provide fundamental information for conservation planning. Pairing these methods is a powerful tool in the study of threatened species, however, they are rarely applied in concert. We examined the mating system and used molecular genetics to measure pairwise kinship and the potential for inbreeding in Hibbertia spanantha, a critically endangered long‐lived shrub endemic to the Sydney Basin, Australia, as a model for conservation planning of species in highly fragmented populations. In situ hand pollination experiments demonstrated that the species is preferentially outcrossing, with limited ability to self‐pollinate (either autogamously or geitonogamously). Although population genetics confirmed high levels of kinship and clonality, there is currently enough population heterozygosity for successful open pollination, primarily through buzz pollination by Sweat Bees ( Lasioglossum [Chilalictus ]). High levels of clonality and population kinship in one population may be the cause of reduced fitness, identified because our outcrossing pollination treatment produced significantly more seeds with greater viability and seed mass than the open treatments. Differences in weight of filled (viable) seeds were identified between populations, although not treatments, where clonal dominance may be swamping pollinator foraging activities. Identification of species mating system, population reproductive capacity, and impacts of fragmentation on population genetic health provides a robust basis for strategic planning and conservation of this critically endangered species, including establishment of an ex situ population and genetic rescue through population augmentation. These methods are easily applicable and particularly relevant to other plant species with small populations or those occurring in fragmented systems. Abstract : Combining population genetics and study of reproductive biology provides robust insights for conservation planning of threatened species.